LEVEL OF MATHEMATICS ANXIETY OF BACHELOR OF ELEMENTARY EDUCATION FRESHMEN STUDENTS - TAGUINOD, DOMARJUN (International Journal of Arts, Sciences and Education, 2022)
This study sets on the belief that mathematics is one of the most difficult subjects in high school even in college and for this reason a teacher should determine the problems that the students are encountering while learning the mathematics subject. Teachers should accept their errors, strengths and weaknesses in order for them to formulate goals and objectives that they want to attain for the development of better programs. Many have claimed that mathematics is something which majority of learners avoid. Some learners are not motivated to study mathematics and they are just contented passing it. With this belief, the researcher is motivated to develop and enrich the mathematics curriculum through constructing a study about mathematics anxiety of the first year students of Bachelor of Elementary Education guided by the research paradigm. The result of the study will give feedback to the first year Bachelor of Elementary Education of Cagayan State University Andrews as to what Level of Mathematics Anxiety they have. The study made use of descriptive-correlational method. The descriptive method is used to investigate if there is significant difference in the level of Mathematics Anxiety of the First Year Bachelor of Elementary Education when grouped according to their profile. The correlational method was used to determine the possible relationship between the physical and emotional factor, assessment factor and social factor that affect the level of mathematics anxiety of the First Year Bachelor of Elementary Education of Cagayan State University Andrews. The study was conducted in Cagayan State University, Andrews Campus particularly in the College of Teacher Education. The College of Teacher Education has three programs namely Bachelor of Elementary Education, Bachelor of Secondary Education and Bachelor of Technical Teacher Education. The data used from this study was collected from the first Year Bachelor of Elementary Education of Cagayan State University Andrews. There were 145 first year students of Bachelor of Elementary Education. Slovin’s Formula and systematic random sampling technique were used to determine the sample population which is 107. In gathering pertinent data in this study, survey questionnaires were used by the researchers. The questionnaire is adopted from an online Mathematics Anxiety Survey created by Kevin Robert (2013) and was used in a written form. The survey question was divided into two parts. The first part is the personal information about the respondents. The second part is the Mathematics Anxiety rating scale. The Mathematics Anxiety rating scale consists of three (3) factors and each factor consist of ten statements that can measure the level of Mathematics anxiety of the respondents. The researcher personally floats the questionnaire to the respondents. The researcher also explained and discussed well how the respondents will answer the questionnaire. Questions regarding what the respondents can’t understand in the questionnaire are being answered by the researcher. The researcher used the frequency and percentage to determine the profile of the respondents. Mean is used to determine the level of Mathematics Anxiety of the respondents in terms of the physical and emotional factor, assessment factor, and social factor. T-Test is used to determine if there’s a difference in the level of Mathematics Anxiety of the respondents when grouped according to sex, school graduated from, honor garnered in high school. ANOVA (analysis of Variance) is used to determine if there’s difference in the level of Mathematics Anxiety of the respondents when grouped according to age and ethnicity. Based on the foregoing findings, the following conclusions were drawn: There is no significant difference on the level of Mathematics Anxiety of the respondents along the three factors when grouped according to age and school graduated from. But when sex, academic performance and ethnicity are concerned, females are more anxious than that of males, non-academic performer respondents are more anxious than academic performer respondents and Ybanag has the highest Mathematics Anxiety among them. Generally, student-respondents are slightly anxious along the three factors in which this implies that they rarely experience mathematics anxiety.